2018
DOI: 10.3390/ijms19113308
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing for Guided Bone Regeneration: A Perspective for Alveolar Ridge Augmentation

Abstract: Three-dimensional (3D) printing has become an important tool in the field of tissue engineering and its further development will lead to completely new clinical possibilities. The ability to create tissue scaffolds with controllable characteristics, such as internal architecture, porosity, and interconnectivity make it highly desirable in comparison to conventional techniques, which lack a defined structure and repeatability between scaffolds. Furthermore, 3D printing allows for the production of scaffolds wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 149 publications
(183 reference statements)
1
78
0
1
Order By: Relevance
“…Some augmentation techniques are complex and involve invasive procedures not well tolerated by patients [4,5]. As a perspective for alveolar ridge augmentation, 3D printing allows for the production of biodegradable and bioresorbable bone scaffolds with patient-specific dimensions using computer-aided design [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Some augmentation techniques are complex and involve invasive procedures not well tolerated by patients [4,5]. As a perspective for alveolar ridge augmentation, 3D printing allows for the production of biodegradable and bioresorbable bone scaffolds with patient-specific dimensions using computer-aided design [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Employing a slurry system (Li, De Wijn, Layrolle, & de Groot, 2002), Wilson et al demonstrated ectopic bone formation and bone buds associated to materials harboring increased surface area implanted in nude mice (Wilson, de, van, Verbout, & Dhert, 2004). Thus, our results emphasized the emergent role of SLA-3D printing in challenging clinical applications such as large alveolar bone defects (Rider et al, 2018). Later, a simpler SLA 3D-printing manufacturing method was developed using and indirect SLA technique but this was not investigated in vivo (Li, Li, Lu, Wang, & Wang, 2007).…”
Section: In Vivo Resultsmentioning
confidence: 81%
“…However, since this technique is based on subtractive manufacturing methods, these clinical reports highlight inherent limitations, such as delayed vascular penetration, slow bone formation, higher rates of bone resorption, possible immunogenicity and disease transmission (Delloye, Cornu, Druez, & Barbier, 2007;Greenwald, Boden, Goldberg, et al, 2001;Zamborsky, Svec, Bohac, Kilian, & Kokavec, 2016), and uncertain osseointegration and fragility (Moles et al, 2018). Therefore, additive manufacturing technologies by stereolithography (SLA) seem to be an excellent approach to process custom-made bone substitute scaffolds to overcome these limits (Rider et al, 2018;Roseti et al, 2017). Light process SLA is one of the most highly developed rapid prototyping techniques and is based upon ultraviolet lightinduced photopolymerization of photocurable resins (Barry et al, 2008).…”
Section: The Advances In Computer Aided Designing and Computedmentioning
confidence: 99%
“…Digital 3D images obtained from CT, MRI or ultrasound, are used to design a suitable scaffold with 3D slicing and CAD software; materials from printing are chosen depending upon the application, and can consist of polymers, ceramics, and bioactive components; cells are selected dependent on the application, a bioink can consist of singular or multiple cell types; post-fabrication 3D culture can be used for characterization, assessment and ultimately implantation. 3D printing is both time and cost effective, enabling fast adjustments and implementation of designs [13]. Designs can be made to match exact defect geometries, improving the union between implant and native tissue, thereby enhancing tissue integration [14].…”
Section: Figurementioning
confidence: 99%